2008
DOI: 10.1103/physrevlett.101.227001
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Vaporization of the Superconducting Condensate in Cuprate Superconductors by Femtosecond Photoexcitation

Abstract: We use ultrashort intense laser pulses to study superconducting state vaporization dynamics in La2-xSrxCuO4 (x=0.1 and 0.15) on the femtosecond time scale. We find that the energy density required to vaporize the superconducting state is 2.0+/-0.8 and 2.6+/-1.0 K/Cu for x=0.1 and 0.15, respectively. This is significantly greater than the condensation energy density, indicating that the quasiparticles share a large amount of energy with the boson glue bath on this time scale. Considering in detail both spin and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
199
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(223 citation statements)
references
References 40 publications
21
199
3
Order By: Relevance
“…With increasing F , A for each component first increases linearly, and then deviates from the linear F dependence. The latter is a signature of saturation and can be associated with the smearing of the gap [2]. The saturation fluence for A s is much lower than that of the fast decay component, which is consistent with the restricted density of states for the SC condensation.…”
Section: Fig 2 (Color Online) T Dependences Of the áR=r Amplitudes supporting
confidence: 50%
See 1 more Smart Citation
“…With increasing F , A for each component first increases linearly, and then deviates from the linear F dependence. The latter is a signature of saturation and can be associated with the smearing of the gap [2]. The saturation fluence for A s is much lower than that of the fast decay component, which is consistent with the restricted density of states for the SC condensation.…”
Section: Fig 2 (Color Online) T Dependences Of the áR=r Amplitudes supporting
confidence: 50%
“…Owing to the high sensitivity in the time domain, the technique allows us to resolve the electronic state stationary points and band extrema near the Fermi energy (E F ). Recently, the framework for analyzing the transient data has being elucidated for various SCES such as high-T c superconductors (SCs) [1][2][3], heavy fermions [4][5][6], transition metal oxides [7], and other related compounds [8]. The application to organic SCES is especially interesting because of their rich variety of electronic ground states which can be tuned by (chemical and/or physical) pressure, temperature, and external fields including photoexcitation [9][10][11][12][13].…”
mentioning
confidence: 99%
“…However, the details of how absorbed photons cause a change of state on ultrafast timescales have so far not been investigated in detail. Recently, a study on La 2−x Sr x CuO 4 (LSCO) single crystals by Kusar et al 1 showed that the energy required to vaporise the superconducting (SC) condensate U v can be determined with reasonable accuracy. These and other measurements on cuprate superconductors since then [2][3][4] give values of U v which are sometimes significantly larger than the experimental condensation energy U c , or the BCS theoretical values 7 , opening the question of mechanism for the destruction of the condensate, the dependence of U v on doping and on the critical temperature T c .…”
mentioning
confidence: 99%
“…1 . A probe wavelength of 800 nm is chosen because it is a well-understood probe wavelength for investigating the superconducting (SC) and pseudogap (PG) response in pump-probe experiments and the best signal/noise ratio as determined by previous studies.…”
mentioning
confidence: 99%
“…Although the interaction of electrons with lattice vibrations is not likely to solely account for the essential properties of high-T c superconductors (HTSCs), many probes including angle-resolved photoemission, [1][2][3][4][5] inelastic neutron scattering, 6 , tunneling 7,8 and Raman 9 spectroscopies have revealed that electron-phonon interactions have significant effects on various properties. Complementary to the timeintegrated techniques, different ultrafast pump-probe techniques [10][11][12][13][14][15] have been used to disentangle microscopic interactions in HTSCs. These techniques aim to study the recombination of photoexcited quasiparticles and the resulting recovery of the superconducting condensate.…”
Section: Introductionmentioning
confidence: 99%